Biological basis of immunomodulatory preparations using in treatment of multiple myeloma - S. V. Semochkin (Онкогематология, 2022)
Immunomodulatory preparations (IMP) — lenalidomide (СС-5013, Revlimid®) and pomlidomide (CC-4047, Actimid®) — a new class of the medical products which are thalidomide synthetic derivatives. In comparison with initial compound they possess higher therapeutic activity and the optimized profile of toxic complications. In this review modern data on IMP antitumor activity with reference to multiple myeloma therapy are presented. Results of clinical study of lenalidomide in first-line therapy, in relapsed/refractory multiple myeloma and as a maintenance therapy after transplantation are shown.